Bingo! Cheating and legally suspect practices in one of North Carolina’s only forms of legalized gambling - Little, Robert (American journal of criminal justice, 1991)
Bingo is one of two legalized forms of gambling in the state of North Carolina. This paper is largely a product of information gleaned from an undercover police operation conducted by a special state task force constructed by the State Attorney General in 1983. The investigation concerned violation of state law designed to regulate bingo activity. This report provides the reader with the development of state law associated with bingo operations, and concentrates on the illegitimate methods used by professional operators to cheat bingo patrons. Legislation designed to crack-down on bingo abuse is discussed as well Gambling is one of the most controversial social activities yet one of the least studied forms of social behavior (King, 1985). Bingo is a specific form of legalized gambling which has received very little attention by social scientists. There have been, however, a few studies which address the characteristics and motivations of bingo players. For example, it has been suggested that bingo is primarily a female activity (Dixie, 1987). However, it has been found that motivations among male and female players differ. Females are motivated more by social contact with other players, whereas men are motivated more by a need for economic advancement (King, 1985). Although some studies exist on the characteristics of bingo players, there is a dearth of research on the operators of bingo games, particularly those operators who ply their trade in a legally suspect fashion. This paper focuses upon the legally suspect mechanisms utilized by some professionals who run bingo gambling operations. The controversy over gambling often extends to state legislatures where lawmakers must wrestle with the question of whether or not to allow legalized gambling within their borders. On the one hand, advocates of legalized gambling cite potential advantages such as the creation of employment opportunities, its potential for enhancement of state revenues, the recreational value of such activity for consumers and the general enhancement of tourism within states having legalized gambling. On the other hand, critics of legalized gambling proclaim its evils such as the perceived relationship of gambling to organized crime, the belief that gambling breeds other social ills (e.g. theft or other crimes of economic desperation) and the belief that gambling can become a psychologically addictive disease which can contribute to individual and family impoverishment as well as community disorganization. North Carolina is one state in which the legislature has demonstrated strong resistance to the allowance of legalized gambling operations. Two exceptions exist, however. North Carolina allows two forms of legalized gambling, bingo games and raffles. This paper focuses upon bingo gambling operations. The central thesis of this paper is bingo was originally legalized to provide tax-exempt, charitable organizations a means of revenue enhancement which would help fund their socially worthwhile endeavors. The legislative changes allowing this form of gambling, however, have created opportunities for professional game operators whose major motivation is personal economic enrichment (versus economic enhancement of charitable organizations). The personal economic enrichment motive is offered to account for the various forms of cheating which were observed in a special investigation of a sample of bingo operations. In a review of theoretical explanations of gambling behavior Kim King (1985) suggests an extension of the functional approach which he labels an “Economic/Status” explanation. This explanation stresses the positive functions of gambling for society and the individual. According to the economic/status explanation, the positive functions of gambling (for the individual) include an innovative opportunity for economic enrichment, success, and status (King, 1985). We would like to suggest that such reasons explain why a number of legally suspect bingo operations have emerged in North Carolina. The same reasons appear to explain the use of various schemes by some bingo operators to cheat their patrons. In short, bingo profits appear to be the primary reason for the massive increase in the number of bingo operations. Other theoretical factors are suggested to account for the attraction of patrons to bingo games. According to King (1985), the “functionalist” explanation of the recent popularity of bingo gambling is due to the tension-release afforded to players of bingo; bingo offers an exciting and innovative way to attain economic success. A concurrent Marxian explanation sees bingo gambling as an opiate of the oppressed, providing a false sense of control and success (King, 1985). Other theoretical factors suggested by King include the symbolic interactionist idea that gambling is a way to display one’s self to others in order to gain character (Goffman, 1967) and the idea that gambling for some people is a means of conspicuous consumption (Veblen, 1899). These factors may account for the popularity of bingo operations, however the focus of this paper is not upon an explanation of why bingo has become so popular. This paper will outline some of the legally suspect methods used by unscrupulous bingo game operators. The information for this report is based upon an undercover police investigation of illegal bingo activity in North Carolina. The investigation was to explore the nature of illegal bingo gambling within the state. Bingo gambling has a unique history in North Carolina; its recent legal history will be discussed in this treatise as well as the various legitimate and illegitimate methods of bingo game operators, state law designed to regulate bingo gambling and measures taken by “professional” (versus “charitable”) operators to protect their lucrative but legally suspect trade.